The Influences of Corporate Social Responsibility (CSR) on Financial Performance in Yemeni Higher Educational Institutions - Al-Hosaini, Fahmi Fadhl; Alazzani, Abdulsamad; Alabsy, Nabil Mohammed; Al-Nashmi, Murad Mohammed; Mohammed, Abdulalem; Hassan, Abdulwadod S. A.; Al-Nabae, Majid (International Review of Management and Marketing, 2025)
The needs for corporations in accomplishing societal values necessitate fostering good business strategies that are purposeful and beneficial. Having corporate social responsibility (CSR) is one of the ways this could be achieved, to boost organizational Financial Performance, particularly for CSR. However, there exists a dearth of empirical studies on the influence of CSR on Financial Performance concerning the higher educational institutions (HEIs) despite their contributions to the international and national economy. The present study focuses on the impact of CSR on the financial performance of Yemeni Universities. The study employed an approach based on a questionnaire survey with the Partial Least Square-Structural Equation Modeling (PLS-SEM) used as the analysis tool. According to the obtained results, CSR has a positive impact on the financial performance of the HEIs in Yemen. This study, therefore, helps in achieving the goals of the HEIs to enhance the universities’ education standards in Yemen.